In vitro and in vivo growth inhibition of human cervical cancer cells via human papillomavirus E6/E7 mRNAs’ cleavage by CRISPR/Cas13a system - Chen, Yili; Jiang, Hongye; Wang, Ting; He, Dan; Tian, Rui; Cui, Zifeng; Tian, Xun; Gao, Qinglei; Ma, Xin; Yang, Jianrong; Wu, Jun; Tan, Songwei; et al. (Antiviral research, 2020)
Sustained infection of high-risk human papillomavirus (HR-HPVs), especially HPV16 and HPV18, is a major cause of cervical cancer. E6 and E7 oncoproteins, encoded by the HPV genome, are critical for transformation and maintenance of malignant phenotypes of cervical cancer. Here, we used an emerging programmable clustered regularly interspaced short palindromic repeat (CRISPR)/Cas13a system to cleave HPV 16/18 E6/E7 messenger RNAs (mRNAs). The results showed that customized CRISPR/Cas13a system effectively and specifically knocked down HPV 16/18 E6/E7 mRNAs, inducing growth inhibition and apoptosis in HPV16-positive SiHa and HPV18-positive HeLa Cell lines, but not in HPV-negative C33A cell line. Simultaneously, we detected downregulation of E6/E7 oncoproteins and upregulation of tumor suppressor P53 and RB proteins. In addition, we used subcutaneous xenograft tumor growth assays to find that the weight and volume of tumors in the SiHa-16E6CR1 group knocked down by the CRISPR/Cas13a system were significantly lower than those in the SiHa-VECTOR group lacking crRNA. Our study demonstrated that targeting HPV E6/E7 mRNAs by the CRISPR/Cas13a system may be a candidate therapeutic strategy for HPV-related cervical cancer. [Display omitted] •CRISPR/Cas13a system was designed and constructed to cleave HPV 16/18 E6/E7 mRNAs.•CRISPR/Cas13a system effectively and specifically knocked down E6/E7 mRNAs and restored P53 and RB proteins.•CRISPR/Cas13a system induced growth inhibition and apoptosis in human cervical cancer cells.•CRISPR/Cas13a system suppressed tumor growth in vivo effectively and specifically.